Analysis on the current status of E -Learning in Colombia Education - Simanca H, Fredys A.; Blanco G, Fabián; Carreño H, Pablo E. (IJRDO- Journal of Educational Research, 2017)
E-Learning is defined as one of the uses of Internet to support learning and is characterized because there is a physical separation between teacher and student, through which a didactic interaction is developed. The student becomes the center of the formation, the manager of his own knowledge, naturally with the help of his tutor and classmates. The learning process is an autonomous work using E-Learning tools which integrates synchronous and asynchronous learning same that is expected to be motivated by a student research process. It is possible to consider that for the actors (tutor, student and community) is a "face-virtual" experience and you can live a self-determining process in the generation of knowledge. However, if the model is enriching, seemingly from every point of view, it is not displayed from the same perspective in the academic modality of undergraduate, where restless little development that have authoring tools in the context of E-Learning. This is the analysis that we seek to address, generating a debate about this subject, in the same way that it is to recognize if there is a contribution or not to the educational model or the subject of this chapter